1993
DOI: 10.1111/j.1365-2141.1993.tb03205.x
|View full text |Cite
|
Sign up to set email alerts
|

Two chronic myelogenous leultaemia cell lines which represent different stages of erythroid differentiation

Abstract: We established two cell lines, YN-1 and Y-1K, from the peripheral blood of two chronic myelogenous leukaemia patients in blastic crisis. Characterization of the YN-1 and Y-1K cells revealed that these cells expressed erythroid lineage markers. However, there was a marked difference in the level of gamma-globin mRNA and haemoglobin in YN-1 and Y-1K cells. YN-1 contained approximately 1-5% benzidine-positive staining cells, whereas no benzidine-positive cells were observed in Y-1K cells. Haemoglobin production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Recently, we reported that hypoxia increased heme contents in YN‐1 cells after 48 h of incubation [8], which prompted us to examine whether hypoxia induces terminal differentiation of erythroid cells. In this context, it has been reported that YN‐1 cells predominantly produce hemoglobin Bart’s, hemoglobin Portland, and hemoglobin F [7]. Each of these hemoglobins contains γ‐globin chains.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that hypoxia increased heme contents in YN‐1 cells after 48 h of incubation [8], which prompted us to examine whether hypoxia induces terminal differentiation of erythroid cells. In this context, it has been reported that YN‐1 cells predominantly produce hemoglobin Bart’s, hemoglobin Portland, and hemoglobin F [7]. Each of these hemoglobins contains γ‐globin chains.…”
Section: Resultsmentioning
confidence: 99%
“…1C). Higher heme content may reflect hemoglobin production in YN‐1 and K562 cells [33,34]. In fact, the population of hemoglobin‐positive cells was about 4.4% in YN‐1 cells and 4.9% in K562 cells under basal conditions [19].…”
Section: Resultsmentioning
confidence: 99%
“…YN‐1 human erythroleukemia cells [27] were maintained in Iscove ’ s modified Dulbecco ’ s medium (Sigma‐Aldrich). K562 human erythroleukemia cells and Jurkat human lymphoblastic cells were maintained in RPMI‐1640 (Wako Pure Chemical Industries).…”
Section: Methodsmentioning
confidence: 99%